Combined treatment for a rare malignant glomus tumor of the esophagus with pulmonary and liver metastases: a case report and review of literature - Liu, Yanan; Mao, Jingjing; Shen, Dongfeng; Jin, Baoli; Wu, Xueqin; Song, Congcong; Du, Wenjing (Frontiers in Oncology, 2024)
Background Glomus tumors are typically benign soft tissue tumors that occur at the extremities; malignant and viscerally occurring cases are extremely rare. Case presentation We report a 49-year old male patient with a malignant esophageal glomus tumor that was complicated by lung and liver metastases. Genetic test results guided the patient’s individualized treatment. Consequently, treatment with Anlotinib combined with Tislelizumab achieved significant clinical benefits. Conclusion Our case report demonstrates that immunotherapy combined with anti-angiogenic therapy in patients with malignant esophageal glomus tumors can achieve significant efficacy and suggests the potential value of next-generation sequencing (NGS) detection in guiding personalized treatments in patients with malignant esophageal glomus tumors.